Answer to Question #245013 in Differential Equations for Niddhi

Question #245013
dx/(x^2-y z) =dy/(y^2-zx)=dz/(z^2-xy)
1
Expert's answer
2021-10-01T13:18:39-0400
"\\dfrac{dx }{x^2-yz}=\\dfrac{dy}{y^2-zx}=\\dfrac{dz}{z^2-xy}"

Taking the multipliers "y, z, x," then the ratio,

"\\dfrac{ydx+zdy+xdz }{x^2y-y^2z+y^2z-z^2x+xz^2-x^2y}"

"=\\dfrac{ydx+zdy+xdz }{0}"

Hence


"ydx+zdy+xdz=0"

Integrate


"xy+yz+zx=c_1"

Taking the multipliers "xy, xz, x^2," then the ratio,

"\\dfrac{xydx+xzdy+x^2dz }{x^3y-xy^2z+xy^2z-z^2x^2+x^2z^2-x^3y}"

"=\\dfrac{xydx+xzdy+x^2dz }{0}"

Hence


"xydx+xzdy+x^2dz=0"

Integrate


"\\dfrac{x^2y}{2}+xyz+x^2z=\\dfrac{c_2}{2}"

"x^2y+2xyz+2x^2z=c_2"

Therefore the solutin is


"\\Phi(xy+yz+zx,x^2y+2xyz+2x^2z )=0"

where "\\Phi" is an arbitrary function.


Need a fast expert's response?

Submit order

and get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

Comments

No comments. Be the first!

Leave a comment

LATEST TUTORIALS
New on Blog